The Anti-Acne Effect of Near-Infrared Low-Level Laser Therapy - Szymańska A; Budzisz E; Erkiert-Polguj A (Dove Medical Press, 2021)
Anna Szymańska,1 Elzbieta Budzisz,1 Anna Erkiert-Polguj2 1Department of Cosmetic Raw Materials Chemistry, Faculty of Pharmacy, Medical University of Lodz, Lodz, Poland; 2Department of Cosmetology and Aesthetic Dermatology, Faculty of Pharmacy, Medical University of Lodz, Lodz, PolandCorrespondence: Anna Erkiert-PolgujDepartment of Cosmetology and Aesthetic Dermatology, Faculty of Pharmacy, Medical University of Lodz, Muszynskiego Street 1, Lodz, 90-151, PolandEmail anna.erkiert-polguj@umed.Lodz.plBackground: Acne vulgaris is a skin problem affecting many people of different ages. Phototherapy is one of the acne treatment options. The aim of the study was to assess the effect of near-infrared low-level laser therapy on acne lesions.Materials and Methods: The prospective study involved a total number of 27 women, aged 18 to 45 years, with mild to severe acne. All the participants underwent a series of six treatments with the use of a 785 nm low-level laser with the power density 80mW/cm2, performed every two weeks. The analysis of the effectiveness of the performed procedures was based on sebumetric examination, photographic documentation and assessment of the change in the number of acne lesions.Results: Significant improvements in acne lesions (assessed as non-inflammatory and inflammatory lesion counts) and a significant decrease in skin sebum excretion were observed after the treatment. No adverse effects were reported.Conclusion: A series of six treatments using a near-infrared low-level laser represents a safe and effective non-invasive therapy option for acne vulgaris.Keywords: low-level laser therapy, acne, near infrared, sebum